The Influence of Wet Scrubber on the Performance Efficiency of Heat Exchanger at Gasification Based Waste to Energy Power Plants - Regina N. Lumbantoruan; Damora Rhakasywi; Fahrudin; Fazli Iqbal Pasha; Putty Fauthyda Z. H.; Firmansyah (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
This research investigates the influence of wet scrubber installation on the performance efficiency of a shell and tube heat exchanger operating in a gasification-based Waste-to-Energy (WtE) power plant located in Surakarta, Indonesia. The study was conducted using a quantitative comparative approach over a four-month operational period, comparing system performance before and after the application of a wet scrubber. Three key parameters such as heat exchanger effectiveness, fouling factor, and pressure drop were analyzed to determine the impact of the gas cleaning system on thermal performance. The results show that the fouling factor decreased from 0.003 to 0.002 J/h·m²·°C, indicating cleaner heat transfer surfaces. Meanwhile, the pressure drop on the tube side reduced from 130.374 Pa to 46.134 Pa, reflecting smoother gas flow and lower mechanical resistance. Consequently, heat exchanger efficiency increased dramatically from 34% to 83%, signifying a substantial improvement in heat transfer capability. These findings confirm that the wet scrubber effectively minimizes tar and fine particulate deposits in syngas, improving heat transfer efficiency, operational stability, and equipment lifespan. The integration of wet scrubbers is therefore proven to be a vital enhancement for optimizing gas cleaning and energy conversion processes in Waste-to-Energy systems.